1996
DOI: 10.1002/(sici)1097-0207(19960315)39:5<829::aid-nme884>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization Using a New Local Approximation Method

Abstract: SUMMARYA new method for solving structural optimization problems using a local function approximation algorithm is proposed. This new algorithm, called the Generalized Convex Approximation (GCA), uses the design sensitivity information from the current and previous design points to generate a sequence of convex, separable subproblems. The paper contains the derivation of the parameters associated with the approximation and the formulation of the approximated problem. Numerical results from standard test proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(57 citation statements)
references
References 15 publications
0
54
0
3
Order By: Relevance
“…Sine dataset function has been testing on different nature inspired meta-heuristics. On the basis of obtaining results, we observe that modified variant of grey wolf optimizer provides extremely accurate solutions on this dataset as can be inferred from test error in Table 10 [51], cuckoo search (CS) [51], method of moving asymptotes (MMA) [51], Grid based clustering algorithm -I and II (GCA-I and GCA-II) [52] and Symbiotic Organisms Search (SOS) [53].…”
Section: Sine Dataset Functionmentioning
confidence: 75%
“…Sine dataset function has been testing on different nature inspired meta-heuristics. On the basis of obtaining results, we observe that modified variant of grey wolf optimizer provides extremely accurate solutions on this dataset as can be inferred from test error in Table 10 [51], cuckoo search (CS) [51], method of moving asymptotes (MMA) [51], Grid based clustering algorithm -I and II (GCA-I and GCA-II) [52] and Symbiotic Organisms Search (SOS) [53].…”
Section: Sine Dataset Functionmentioning
confidence: 75%
“…A.2 Two-bar truss design problem [8] The two-bar truss problem consist of two design variables: a sizing variable x 1 which is the cross-sectional area of the bars and the configuration variable x 2 representing half the distance between the lower nodes. An external force, |F | = 200kN , F y = 8F x , acts on node 3 and the objective is to minimize the weight of the truss while keeping the tensile or compressive stress in each bar below 100N/mm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…A.1 Cantiliver design problem [8] The Cantilever beam is made of five elements, each having a hollow crosssection with constant thickness. The beam is rigidly supported as shown, and three is an external vertical force acting at the free end of the cantilever.…”
Section: A Appendixmentioning
confidence: 99%
“…However, the authors have not seen any studies that have found this solution in the literature. Slightly higher values have been found by cuckoo search and other methods [ [Chickermane and Gea (1996), Gandomi et al (2013)]]. The best solution found so far by [Gandomi et al (2013)] is…”
Section: Cantilever Beam Design Benchmarkmentioning
confidence: 99%